Philippines’ Government Sponsored Health Coverage Program for Poor Households - Chakraborty, Sarbani (World Bank, Washington DC, 2013)
This is a nuts and bolts case study of the implementation of the government-financed health coverage program (HCP) for poor households in the Philippines. The data and information in this case study largely draws upon the 2011 World Bank Report 'Transforming the Philippine health sector: challenges and Future Directions' (Chakraborty et al. 2011), and technical work undertaken for World Bank support to the Government of the Philippines (GOP) for universal health coverage (UHC) in the Philippines.2 The aim of the case study is to understand how the HCP was implemented, what worked and did not work, and how it impacted expected results under the HCP. In 1996, similarly to many low- and middle-income countries, the Philippines introduced a demand-side program for poor households (the Sponsored Program). The objective was to improve access of poor households to needed health services without experiencing a financial burden. Unlike many countries, where such programs are stand alone, in the case of the Philippines it was integrated into the National Health Insurance Program (NHIP). This is a sound design feature from the perspective of providing optimal risk pooling and redistribution, and the Philippines is a model for other countries implementing similar schemes for poor households. The national government has included financing for poor households in the medium-term national expenditure program, so there is no danger of uncertainty in financing. PhilHealth is incrementally strengthening its contract implementation and monitoring mechanisms. The main challenge now facing the HCP is whether these revamped efforts will be able to quickly address the problem of lack of access to quality and affordable services for poor households. There are supply side constraints, facilities will need to be upgraded to obtain Philhealth accreditation. Accredited health facilities will have to be held accountable for delivering services and where public services are not available, mechanisms for incentivizing the private sector for outreach to poor households will have to be deployed. Much depends on Phil Health's capacity as an effective purchaser of health services. Local government unit (LGU) facility capacity to respond to revamped PhilHealth incentives is another bottleneck. The other challenge is whether the Department of Health and PhilHealth will be able to quickly build the monitoring and evaluation systems needed to track HCP implementation and make the necessary in-flight adjustments in implementation in a timely manner.